"Contribution à l'étude de l'approche numérique pour l'estimation des débits solides d'Oued Righ – Touggourt- " - تي, يوسف; مستور, الجندي; بالمسعود, محمد شاكر (Université d'El Oued, 2022)
"Oued Righ Main Channel is primarily responsible for drainage of dirty water, house water and exess agricultural water as it has effect of lowering the water level of free-layer, And peasant water. That’s why we have conducted a Technique study on the composition and origin of «Oued RIgh Channel» and the problems associated with it, as well as the study of the ground geological and hydrological layers and the study of the climatic conditions of this region. For the hydraulic study of the channel, we chose 10 stations along the channel that are suitable study points to calculate the hydraulic characteristics :( the flou, medium speed, of flow as well as flow quality. and other calculations. We have used the numerical calculation method using the Excel program for several scientists in order to transport solids based on previous studies on the channel Finally, after integrating the relationships, we found an identical relationship with one of the most famous scientists in the study of solid transport, and the results were very close if not identical. " "تعتبر قناة وادي ريغ هي المسؤولة بشكل اساسي عن تصريف المياه القذرة والمنزلية والمياه الفلاحية الزائدة، وحيث انها لها تأثير على خفض المياه في الطبقة الحرة والمياه الفلاحية. من اجل هذا قمنا بدراسة تقنية حول تكوين وأصل القناة وادي ريغ ومشكلة النقل الرواسب بهذه القناة وكذلك دراسة الظروف المناخية في هذه المنطقة من اجل الدراسة الهيدروليكية، اخترنا 10 عشر محطات على طول القناة، وهي تمثل نقاط دراسة مناسبة لحساب الخصائص الهيدروليكية التدفق، السرعة المتوسطة للجريان وكذلك نوعية التدفق وغيرها من الحسابات. وقد استعملنا طريقة الحاسب الرقمي بواسطة برنامج الاكسل لعدة علماء في نقل الرواسب انطلاقا من دراسات سابقة عن القناة وفي الاخير وبعد دمج علاقات وجدنا علاقة متطابقة مع أحد أشهر العلماء في دراسة النقل الرواسب وكانت نتائج متقاربة جدا ان لم نقول متطابقة. "
مذكرات ماستر تخصص ري
Keywords: Oued Righ – Oued Righ Canal – solid transport – Numerical approche- Excel program.; واد ريغ، قناة واد ريغ، نقل الرواسب، دمج العلاقات، برنامج الإكسل.